Analisis Pengaruh Promosi dan Word of Mouth terhadap Minat Mahasiswa Menggunakan Produk Perbankan Syariah - Yolanda, Agnisha; Ramadhani, Raigis Putri; Sendi, Sendi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2025)
This research explores how advertising and word-of-mouth affect students' interest in Islamic banking. Using a quantitative survey of 120 students and multiple linear regression analysis, the study found that both promotional efforts and word-of-mouth referrals positively and significantly impact student interest. However, word-of-mouth proved to be the more powerful influence. The findings emphasize the value of experiential marketing and peer influence in promoting Islamic banking services to students.